Pol Roti : A Shining Star in the Shadow of Rotis: The Nostalgia of Pol Roti (International Journal of Scientific Research and Management (IJSRM), 2024)
Pol roti, a Sri Lankan dish, filled me with anticipation as I waited for my mother to finish cooking it. There was something magnetic about its aroma, simple ingredients, and how it brought the family together around the dinner table. This essay explores pol roti’s cultural, historical, and personal significance in my life and my family’s heritage. This dish has flour, coconut scraps, green chili, and onions. There is a strong aroma of coconut scraps, and you can smell the spice of the chili. Green chili pepper is a key ingredient that adds a fiery, vibrant kick to the dish. This is often used to balance the sweetness of other ingredients.